Active aging and urban policies: the space as an instrument for an inclusive and sustainable city - Carrera, Letizia (Frontiers in Sociology, 2023)
Aging is one of the most important challenges of our times. «Policies to meet the challenge of a growing, healthier and more active elderly population -based on the view of the ageing of society as an opportunity to be utilized -automatically benefit the individual ageing person, materially and otherwise.Similarly, any effort to ameliorate the quality of life for the elderly, and to meet their diverse social and cultural needs, enhances their capacity to continue interacting with society» (UN, 1983). Aging society provides not only a new context, but a new opportunity to rethink our traditional views of age. The growing number of elderly people will soon make the majority of overall population. As noticed by reports of international organizations, cities will play a more important role in dealing with these quantitative and cultural changes, mostly because it is expected that a quarter of the population over60 will be concentrating in the central areas of compact cities. In brief, cities are at once growing and aging at an incredible speed. Although aging process represents a fundamental and structural phenomenon with very deep consequences at economic, social and political level, and with an impact on the individual one as on the society as whole, our cities should deal with this process and respond, in terms of public health and social care, to needs of older people, also those that will experience a loss of autonomy. It is important to note that there are a greater heterogeneity within older population in terms of conditions and demands, which depend on their specific personal, social and familial context. Urban space - in its complex differentiation between public space, third space, and private space - represents both a tool and a strategic factor in pursuing the objective of ensuring high levels of widespread well-being and, from a political perspective, fully shaping the right to the city for elderly individuals.